Closed-Loop Synergistic Nitric Oxide/Hydrogen Delivery with Feedback Control for Diabetic Wound Healing - Wen, Pengfei; Luo, Pan; Gao, Fuqiang; Yang, Mingyi; Li, Junyou; Yang, Zhi (Nano-Micro Letters, 2026)
Dynamic treatment represents the cornerstone of precision medicine. However, the development of closed-loop systems that respond to endogenous biomarkers remains challenging. Here, we report a dual-channel flexible electrocatalytic system (Pd-Ni5P4/DCEFS) integrated into a microneedle array that enables ultrasensitive real-time monitoring of nitric oxide (NO)—a key biomarker of wound inflammation—with a detection limit of 9.6 nM, while simultaneously driving the hydrogen evolution reaction with a low overpotential of − 91.0 mV at − 10 mA cm−2. This integrated platform establishes a closed-loop sensing-feedback-intervention mechanism, enabling NO-guided on-demand hydrogen generation for precision anti-inflammatory treatment. In diabetic mouse skin wound models, this adaptive hydrogen production strategy markedly suppresses inflammation, promotes tissue regeneration, achieves substantial wound closure within 5 days, and reduces the overall healing time to 11 days. This study establishes a new paradigm for closed-loop dynamic treatment of inflammatory diseases and provides a critical foundation for next-generation self-adaptive therapeutic platforms in regenerative medicine. Highlights: 1 Pd-Ni5P4/dual-channel electrocatalytic flexible system (DCEFS) employs a bifunctional catalyst, dual-channel electrodes, and microneedle array to achieve continuous, decoupled-free coupling of nitric oxide sensing and hydrogen treatment. 2 Pd-Ni5P4/DCEFS pioneers a single-cycle “sense-hydrogen treatment-sense” strategy for closed-loop inflammation resolution, delivering efficient reactive nitrogen species/reactive oxygen species clearance with real-time nitric oxide-based feedback for precise therapeutic control. 3 Pd-Ni5P4/DCEFS innovatively establishes a closed-loop ‘sense-hydrogen treatment-sense’ paradigm guided by lesion-specific NO levels, enabling on-demand hydrogen intervention to potently resolve inflammation, robustly drive tissue regeneration, and markedly accelerate diabetic wound healing with excellent biocompatibility.